LEARNING FROM THE PAST TO PREPARE FOR THE FUTURE: A REVIEW OF RESEARCH OUTPUT ON POSTGRADUATE EDUCATION IN DESIGN AT THE FACULCITY OF VISUAL ART AND DESIGN, ITB (2015-2018) - Achmad Syarief; Yan Yan Sunarya (Fakultas Seni Rupa dan Desain ITB, 2019)
Recent technological advancement and the betterment of socio-cultural welfare put design knowledge at the forefront of life as its practice develops into more than 'activity of making'. Rapid prototyping, 3D printing, internet-of-things, and wide array of networking channels may ease the burden of producing objects. For the past 20 years, the practice of design has addressed 'activity of research' beyond previous ordinary know-how in making object. Indonesia